Effects of Eucalyptus Plantations on Detritus, Decomposers, and Detritivores in Streams - Manuel A.S. Graça; Jesus Pozo; Cristina Canhoto; Arturo Elosegi (The Scientific World Journal)
Vast areas of the Iberian Peninsula are covered by monocultures of the exotic tree Eucalyptus globulus. Given that (1) leaf litter produced in the riparian areas is the main energy source for small streams, and (2) trees differ in their nutrient content, chemical defenses, and physical attributes, eucalypt plantations have the potential to affect the biology of streams. Research teams from the University of Coimbra and the University of the Basque Country have been addressing the potential effects of eucalypt plantations at several levels of study. Here we review the main conclusions of these investigations.